SSV-Robustness Analysis of Disturbance Observers with Active Steering Control Application - Güvenç, Bilin Aksun; Güvenç, Levent (Elsevier BV, 2003)
Abstract While standard robust stability analysis of the disturbance observer in the presence of unstructured modeling error is well known and results in a simple design guideline, similar results are lacking for the case of structured, real parametric and mixed uncertainty in the plant. Considering the case in which the plant has both real parametric uncertainty and complex uncertainty due to high frequency unmodeled dynamics, the mixed structured singular value method is applied to stability and performance robustness analysis of disturbance observer compensated systems, with an active car steering control example used to illustrate the method.